Extracting material parameters of silicone elastomers under biaxial tensile tests using virtual fields method and investigating the effect of missing deformation data close to specimen edges on parameter identification. Issue 27 (14th December 2022) - Jiang, Mingliang; Wang, Zhujiang; Freed, Alan D.; Moreno, Michael R.; Erel, Veysel; Dubrowski, Adam
Abstract: In this work, virtual fields method (VFM) is applied to extract the constitutive parameter of silicone elastomers under equi-biaxial and general biaxial tests; the influence of missing deformation data near specimen edges and noise introduced by digital image correlation (DIC) on parameter identification using VFM is investigated. The results indicate that the negative impact of the missing data and noise can be mitigated by scaling the load applied to the specimen boundary properly and extracting parameters based on the deformation fields of all loading steps through the least square method.